The role of counterion on the thermotropic phase behavior of DODAB and DODAC vesicles - Feitosa, Eloi [UNESP]; Alves, Fernanda Rosa (Elsevier B.V., 2008)
Diocradecyldimethylammonium bromide and chloride surfactants (DODAX, X representing Br(-) or Cl(-) counterions) assemble in water, above their melting temperatures (T(m)), as cationic unilamellar vesicles at the typical surfactant concentration of 1.0 mM. The larger T(m) of DODAC (49 degrees C) relative to DODAB (45 degrees C) has been attributed to the differing affinity and binding specificity of the counterions to the vesicle interfaces. In this communication it is reported differential scanning calorimetry (DSC), conductimetry and dynamic light scattering (DLS) data for mixtures of DODAB and DODAC in water at 1.0 mM total surfactant concentration and varying surfactant concentration, to investigate the effect of counterion on the pre-, main- and post-transition temperatures (T(s), T(m) and T(p)), and the data compared to the neat surfactants in water. Accordingly, T(m) increases sigmoidally from 45.8 to 48.9 degrees C when DODAC molar fraction (x(DODAC)) is varied from 0 to 1. Neat DODAB exhibits in addition to T(m), T(s), and T(p) that are inhibited by DODAC. The main peak width Delta T(1/2) does not depend on the surfactant molar fraction but the melting enthalpy change Delta H is smaller for DODAB-rich dispersions due to the stronger affinity of Br(-). The conductivity and the apparent hydrodynamic diameter as well do not vary Much With x(DODAB), indicating that the surface charge density is similar for DODAB and DODAC, evidencing the role of the counterion binding specificity and affinity on the properties of DODAX vesicles. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: DODAB; DODAC; DSC; Dynamic light scattering; Conductivity; Cationic vesicle; Melting temperature